Horrible Harry goes to the moon - Kline, Suzy.; Remkiewicz, Frank (New York : Viking, 2000)
Inspired by his third-grade class's study of the moon, Harry announces that he is going there.
G2
Keywords: Schools -- Fiction; Moon -- Fiction